Systematic analysis of reproductive development in normal and mantled oil palm (Elaeis guineensis Jacq) flowers and fruit - Unnikrishnan, Jennie (2023)
Oil palm (Elaeis guineensis Jacq.) is the most efficient oil crop in the world; it uses substantially less land and resources and produces more oil than any other oil crop. Even so, to meet the growing palm oil demands due to the increasing global population, per capita consumption rates and biofuel demands, ground-breaking strategies for agronomic and genetic improvement of the commercial planting material are necessary. Clonal propagation through tissue culture has proven to be useful in producing uniform planting materials. However, there are incidences of the deleterious floral homeotic mutant, mantled, in oil palm ramets.